Comparative susceptibility of transgenic Bt cotton hybrids to Earias spp. and other non-target insects. (May 2015) - Shera, P.S.; Arora, Ramesh; Singh, Pritpal
Abstract: Four Bt cotton ( Gossypium hirsutum L.) hybrids, each with one of four different events, viz ., MRC 6301 Bt ( cry1Ac gene), JKCH 1947 Bt (modified cry1Ac gene), NCEH 6R Bt (fusion cry1Ac / cry1Ab gene) and MRC 7017 Bollgard II ( cry1Ac and cry2Ab genes) were evaluated along with their respective isogenic non-Bt genotypes against Earias spp., sucking insect pests, and predators in 2010 and 2011. Female oviposition was not significantly different between Bt and non-Bt cotton hybrids. All Bt cotton hybrids recorded significantly reduced damage of Earias spp. in shoots, squares, green bolls and freshly shed fruiting bodies as compared to the isogenic non-Bt genotypes. In 2010, the incidence of Earias spp. was observed only on 136 day old crop or later. MRC 7017 Bollgard II had the lowest damage followed by NCEH 6R Bt, MRC 6301 Bt and JKCH 1947 Bt. However, no damage was observed in any of the Bt hybrids throughout the cropping season in 2011. The time of first appearance of Earias spp. on Bt cotton differed from non-Bt genotypes, whereas, first appearance of sucking insects and predators did not differ between Bt and their isogenic non-Bt genotypes. Populations of sucking insect pests Amrasca biguttula biguttula (Ishida), Bemisia tabaci (Gen.) and Thrips tabaci (Lindemann) varied significantly among different cotton genotypes. Nevertheless, their incidence on Bt cotton hybrids did not differ significantly from the respective isogenic non-Bt genotypes. No significant differences were observed with respect to relative abundance of predators, viz ., spiders, chrysopids and coccinellids on Bt and non-Bt cotton genotypes. All Bt cotton hybrids out-yielded their isogenic non-Bt genotypes during both years. The yield was significantly higher in MRC 7017 Bollgard II followed by MRC 6301 Bt, NCEH 6R Bt and JKCH 1947 Bt. The selection of superior genotypes with better yield characteristics is thus vital for developing high yielding transgenic cotton. Highlights: Female oviposition was not significantly different between Bt and non-Bt cotton hybrids. Bt cotton hybrids recorded significantly reduced damage of Earias spp. as compared to their isogenic non-Bt genotypes. MRC 7017 BG II showed lower damage followed by NCEH 6R Bt, MRC 6301 Bt and JKCH 1947 Bt. Bt toxins had no apparent effect on sucking insect pests and predatory fauna. All the Bt cotton hybrids out-yielded their isogenic non-Bt genotypes.